Role of Regulatory T Cells in Infection and Vaccination During Early Infancy - Funes, Samanta C.; Mansilla, Miguel A.; Canedo-Marroquín, Gisela; Lay, Margarita K.; Riedel, Claudia A.; Kalergis, Alexis M. (Current Pharmaceutical Design, 2018)
Reducing infant mortality due to infectious diseases is one of the most important public health goals worldwide. Several approaches have been implemented to reach this goal and vaccination has been an effective strategy for reducing infant and newborn mortality. However, the immunological features of neonates and infants represent a significant barrier to the effectiveness of vaccination. Since regulatory T cells (Treg cells) are known to play an active role in contributing to various mechanisms of suppression of the immune cell function. It has been proposed that these immune cells could decrease the immunogenicity of vaccines administered in newborns and infants. In this article, we discuss the various types of Treg cells, along with their suppressing and inhibitory mechanisms, which are used by these cells in the context of infectious and immunization processes in newborns and infants.
Keywords: infants